“I Have Grown Accustomed to Being Rejected”: EFL Academics’ Responses Toward Power Relations in Research Practice - Lu, Hua; Yoon, Sook Jhee (Frontiers in Psychology, 2022)
While there has been an increasing interest in English as a foreign language (EFL) teachers’ research engagement and researcher identity construction, scant attention has been paid to tensions caused by the issue of power relations in their research practice. This study draws on data from semi-structured interviews complemented with data from narrative frames and document analysis to examine the influence of power relations on the research practice of six EFL academics and their coping strategies at a Chinese university. The data analysis reveals that for the participants in the study, even though they were driven to be engaged in research practice by a combination of intrinsic and extrinsic motivations, they found that their research endeavors were undermined by the marginalized status of EFL researchers from non-elite universities, as imposed by the Chinese academic circle. Nevertheless, in the face of potential bias against their peripheral academic status, they exerted their agency with micropolitical literacy and tried to seek a way out of the unfavorable academic culture. As EFL teachers at regular universities are increasingly expected to be more research-active and research-productive, more attention and support are needed to facilitate their professional development and researcher identity construction.